Chinese Soft-Shelled Turtle Oil in Combination With Swimming Training Improves Spatial Memory and Sports Performance of Aging Rats - Chia-En Yang; Tsung-Ming Yeh; Tsung-Ming Yeh; Ching-Dong Chang; Wen-Ling Shih (Frontiers in Physiology, 2021)
In this study, waste fat from the Chinese soft-shelled turtle (Pelodiscus sinensis) was used as the raw material, and soft-shelled turtle oil (SSTO) was extracted by water heating. Analysis of the fatty acid composition of SSTO revealed that unsaturated fatty acids (UFAs) comprised more than 70% of the oil, of which more than 20% were omega-3 poly-UFAs. DPPH radical scavenging and cellular ROS assays confirmed the reduction of oxidative stress by SSTO. In D-galactose-induced aging rats, SSTO feeding alone or in combination with swimming training resulted in improved memory and physical strength. In addition, SSTO feeding with swimming intervention significantly increased the SOD level and maintained better blood pressure in the aged rats. The serum DHEAS and soleus muscle glycogen level were also highly correlated with SSTO feeding and swimming training. In conclusion, the results of this study demonstrated that SSTO has the potential to be developed into a health food that exerts anti-aging effects, and those effects are stronger when combined with daily swimming exercise.